Pengaruh Orientasi Kewirausahaan, Inovasi, dan Kreativitas Produk terhadap Keunggulan Bersaing pada Usaha DR. Spicy Cepu - Fadhillah, Islah; Novaria, Rachmawati; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACTIn this study, the researcher will explain the test of several factors that can influence Competitive Advantage, which are Enterpreneurial Orientation, Innovation, and Product Creativity in the business of DR. Spicy Cepu. To be able to know the effect of Entrepreneurship Orientation, Innovation, and Competitive Advantage, so researcher used quantitative research methods for maximum results, with survey research using questionnaire as an instrument. The sample of this study used a non-probability sampling method (non-random sampling) using a purposive sampling technique of 100 respondents. The data analysis technique used is multiple regression analysis. The population of this study are consumers who have consumed products from DR. Spicy Cepu.Data from respondents were collected through distributing questionnaires that had been tested for Validity and Reliability Tests. From the validity test, it is obtained that the r value of all items is greater than the value of r table (0.361), so it is stated that the questionnaire is valid, and from the reliability test, the cronbach alpha value> 0.60 is obtained so that it can be concluded that the questionnaire is reliable. The results of this study indicate that all independent variables namely Entrepreneurial Orientation, Innovation, and Product Creativity have a positive influence on the dependent variable namely Competitive Advantage.Keywords: Entrepreneurship Orientation, Innovation, Product Creativity, and Competitive Advantage